Regeneración ósea guiada con hidroxiapatita y carbonatos de calcio como relleno óseo en parietal de conejos New Zeland - Reátegui Navarro, Marco Antonio (2008)
The present work of experimental, comparative and longidinal character was based on the use of biomaterials that allow to prevent or to refill the bone defects in maxillas. Existing material of origin synthetic and natural as calcium carbonate in whose composition contains elements similar to the Hidroxiapatita of the bone. The positioning of the membrane of collagen on the bone fillings to exclude the not desire tissues denominate Guide Bone Regeneration. The Objective of this investigation is: To compare the degree of guided bone regeneration between the Hidroxiapatita and Calcium Carbonate like bone filling in the parietal of rabbits New Zeland. 27 male rabbits of New Zeland race of 03 months of age were used, which were separated in 03 groups: Hidroxiapatita – Control (Ha-C), Carbonate Calcium Synthetic – Control (CCaSC), Carbonate Calcium Natural – Control (CCaN-C). The results showed that the Ha has behaved as regenerative bone from the first month. In the second month CCaS had similar behavior (p = NS) unlike the CCaN that just after the third month began as bone regeneration (p <0.05). When comparing the results the Ha and has CCaS the boneformation consolidated into the third month and CCaN still in state primary Neoformation bone. The biocompatibility was evident in the three materials varying in adapting and neoformation bone over time.